Spiritual well-being and life satisfaction among older people residing in an urban community of Bhaktapur, Nepal - Sabita Pandey; Sangita Tuitui (Journal of Karnali Academy of Health Sciences)
Background: Spirituality has been shown to predict well-being in old age. Spirituality and fulfillment of spiritual needs are considered priorities in the care of older people. Life satisfaction is influenced by several factors and is also an important issue in the care of older people. This study is intended to assess spiritual well-being and life satisfaction among older people residing in an urban community of Bhaktapur, Nepal.